2015
DOI: 10.1096/fj.15-274001
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated development of IL‐17‐ and IL‐21‐expressing follicular helper T cells and increased germinal center formation in the absence of RORγt

Abstract: Interleukin 17-producing helper T (Th17) cells have been widely defined by the lineage transcription factor retinoid-related orphan receptor (ROR)γt. Pathophysiologically, these cells play a crucial role in autoimmune diseases and have been linked to dysregulated germinal center (GC) reactions and autoantibody production. In this study, we used gene expression and flow cytometric analyses for the characterization of Rorγt(-/-) and Rorγt(-/-)Il21(RFP/+) mice to demonstrate a previously unknown transcriptional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 47 publications
(79 reference statements)
1
20
0
Order By: Relevance
“…). Th17 cells are also a lineage of CD4 + T cells and are characterized by expressing the transcription factor retinoic acid receptor‐related orphan receptors and the cytokine IL‐17, among others. However, Th17 and Treg cells present a certain level of plasticity, meaning that distinct milieus account for distinct cell fate .…”
Section: Origin and Characteristics Of Th17 And Treg Cellsmentioning
confidence: 99%
“…). Th17 cells are also a lineage of CD4 + T cells and are characterized by expressing the transcription factor retinoic acid receptor‐related orphan receptors and the cytokine IL‐17, among others. However, Th17 and Treg cells present a certain level of plasticity, meaning that distinct milieus account for distinct cell fate .…”
Section: Origin and Characteristics Of Th17 And Treg Cellsmentioning
confidence: 99%
“…Notably, the patterns of IRF4 expression observed in the current study were comparable with that of Fyn expression in both SA and normal pregnancy. IRF4 plays a crucial role in immune response and has been proposed as a decisive factor in the IL‐21‐mediated steps of Th17 development, by influencing Foxp3, ROR‐α and ROR‐γt expression . A recent study found that IRF4 expression was reduced during early stage of Th17 cell differentiation in the absence of Fyn .…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 and IL-21 are important for the formation of spontaneous ELS but also for the development of pathogenic autoantibodies in the CNS. The mechanism through which IL-17 is involved in this process is the following: IL17 upregulates signalling proteins that promote the capacity of follicular Th cells to form conjugates with B cells in the light zone of germinal centres in CNS and promotes follicular Th cells differentiation and stabilisation (21,22,24). Furthermore, the germinal centres include both follicular T cells and follicular regulatory T cells that maintain an optimal response in preventing the auto-emergence of the autoreactive B cells (25,26).…”
Section: Th17 Cells and Ectopic Lymphoid-like Structuresmentioning
confidence: 99%
“…There is a close relationship between B cells and Th17 cells, leading to an elevated number of B cells and ELS as a mark for Th17 signature in MS (22,24). Th17 cells promote an inflammatory B cell response inside the CNS through the presence of infiltrating Th follicles (29).…”
Section: Th17 Cells and Ectopic Lymphoid-like Structuresmentioning
confidence: 99%